Sports sponsorship : getting your share / by Brian Sims. - Sims, Brian (Hazleton, 2005)
Brian Sims delivers an insightful and entertaining compendium of tips, case studies and personal accounts dedicated to the serious business of attracting corporate investments into sport - at every level.